Contributions of meaningful experiences gatherings to artistic education field - Bustamante Cardona, Bernardo (Universidad Pedagógica y Tecnológica de Colombia, 2012)
This article shows a theoretical approach to and a description of some contributions of a work of transformation of educational and sociocultural reality carried out by a group of people and institutions, among which are San Buenaventura University, Antioquia Museum, Ediarte Inc. and Antioquia University. Such intervention aims at contributing to the improvement of Artistic Education quality in Antioquia and the nation. In order to understand the significance of these Gatherings, a short historical framework is explained in which global and regional processes of academic activities having an impact on the structure of the Artistic Education field are pointed out. Likewise, some perspectives in the definition of artistic education are tackled and then a definition of Pierre Bourdieu´s concept of fieldis presented. Therefore, Meaningful Experiences Gatherings in Artistic Education (MEGAE) are presented and the three first gatherings are described. Finally, it is shown the panorama of the contributions of the gatherings both in the theoretical formulation and relational structure of the field.